The Humbling Mind: Where Modern Cognition Meets Prophetic Wisdom - Maspul, Kurniawan Arif; Mubarak, Islahuddin Ramadhan (Pubmedia Social Sciences and Humanities, 2025)
In an era besieged by information overload and cognitive arrogance, this interdisciplinary study investigates the perilous “illusion of knowledge”—a phenomenon where overconfidence eclipses genuine understanding, exacerbating societal polarization and intellectual stagnation. Bridging modern neuroscience with Islamic epistemology, the research reveals striking parallels: the brain’s Default Mode Network (DMN), linked to self-referential biases and overconfidence, mirrors the Qur’anic concept of kibr (arrogance), while intellectual humility (tawadu’) emerges as both a neurological and spiritual antidote. Through hermeneutic analysis and global case studies—including Senegal’s daara schools and Singapore’s neuroscience-integrated madrasahs—the study demonstrates how pedagogical models blending metacognitive reflection with ethical discipline enhance cognitive flexibility, critical thinking, and empathy. Findings underscore that 80% of individuals overestimate their competence (Dunning-Kruger effect), yet Islamic practices like muhasabah (self-accountability) and adab (ethical inquiry) counteract this by fostering humility and error detection. The paper critiques algorithmic echo chambers and cultural conditioning, advocating for education systems that harmonize ancestral wisdom (e.g., hikmah) with neuroscientific insights to cultivate fitrah-aligned, morally grounded learners. Moreover this synthesis of prophetic wisdom and cognitive science offers a roadmap to dismantle epistemic arrogance, heal polarized societies, and reorient humanity toward curiosity, compassion, and ethical accountability